Dialek dan Bahasa dalam Sastra Rakyat Kalimantan Tengah: Penggunaan Dialek Lokal dalam Cerpen dan Puisi serta Dampaknya terhadap Identitas Budaya - Maulana Abdurrasyid; Dwi Wahyu Candra Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article discusses the use of local dialects in short stories and poetry from Central Kalimantan, as well as their impact on the cultural identity of the community. Local dialects, such as Dayak and Banjar languages, serve as crucial elements in folk literature that reflect the life, values, and traditions of the people. Through the analysis of literary works incorporating these dialects, the article demonstrates how dialects not only enrich the reading experience but also function as tools for cultural preservation. The use of local dialects in literature helps strengthen cultural identity and a sense of unity within the community. Despite challenges in the application and publication of literature in regional languages, it is essential to continue supporting the use of local dialects to ensure the cultural richness of Central Kalimantan remains preserved and relevant.